Testicular size and reproductive traits as selection criteria of rams - Toe, F. (Institut Agronomique et Veterinaire Hassan II, 1995)
Abattoir, on-farm and market surveys revealed that 30 percent of the Menz rams were unfit for efficient breeding due to sexual disorders, mainly in the form of balanoposthitis, epididymitis and orchitis. On-station study of testicular size in adult rams, semen traits and libido showed that the testicles were larger in Horro rams than Menz but, when adjusted to body weight and heart girth, the only difference resided in testicular length and epididymal tail diameter. Older rams had greater libido and serving capacity than the younger ones. Although the two breeds were considered fertile all year around, their reproductive performance was reduced during the hot dry and beginning of main rainy seasons. December to February was the period of better sexual desire and sperm quality. Testicular and Epididymal diameter were better predictors of sperm production and quality, libido and serving capacity. After testicular measurement at 6, 9 and 12 months of age in ram lambs testicular size was found heritable in Horro and Menz rams and genetically correlated to age at puberty in the females. Trial to determine the dosage and method of injection of lactic acid to sterilize rams demonstrated that chemical castration is efficient using epididymo-testicular injection of 3 ml per testicle of a solution containing 50% of lactic acid. It was concluded that rams can be selected based on testicular size, which is heritable and correlated to semen traits and libido, but such selection should take into account the pathological and phenotypic variations affecting testicular size.